Влияние Сu2+ на синтез поверхностно-активных веществ Аcinetobacter calcoaceticus ІМВ В 7241 и Rhodococcus erythropolis ІМВ Ас-5017 - Пирог, Татьяна Павловна; Конон, Анастасия Дмитриевна; Софилканич (Морозова), Анна Павловна; Шевчук, Татьяна Андреевна; Парфенюк, Сергей Андреевич (My University, 2012)
Исследовали синтез поверхностно-активных веществ (ПАВ) при культивировании Rhodococcus erythropolis ІМВ Ас-5017 и Acinetobacter calcoaceticus ІМВ В-7241 на гидрофобных (н-гексадекан, жидкие парафины, подсолнечное масло) и гидрофильных (этанол) субстратах в зависимости от концентрации (0,01−0,5 мМ) и момента внесения в среду катионов меди. Установлено, что добавление Cu2+ в экспоненциальной фазе роста штаммов ІМВ В-7241 и ІМВ Ас-5017 на всех исследуемых субстратах сопровождалось повышением условной концентрации ПАВ на 25−140 % по сравнению с показателями на среде без катионов меди. Максимальная интенсификация синтеза ПАВ A. calcoaceticus ІМВ В-7241 и R. erythropolis ІМВ Ас-5017 наблюдалась при внесении Cu2+ в среду с углеводородами. Повышение синтеза ПАВ в присутствии катионов меди обусловлено их активирующим влиянием на активность алкангидроксилазы обоих штаммов, а также 4-нитрозо-N,N-диметиланилин-зависимой алкогольдегидрогеназы и ферментов биосинтеза поверхностно-активных глико- (фосфоенолпируват-синтетаза) и аминолипидов (НАДФ+-зависимая глутаматдегидрогеназа) у A. calcoaceticus ІМВ В-7241. Synthesis of biosurfactants (surface-active substances, SAS) was investigated under the conditions of growth of Rhodococcus erythropolis IMV Ac-5017 and Acinetobacter calcoaceticus IMV B-7241 on hydrophobic (n-hexadecane, liquid paraffins, sunflower oil) and hydrophilic (ethanol) substrates depending on concentration (0.01-0.5 mM) and time of copper cations introduction in the medium. It is established that Cu2+ addition in the exponential phase of growth of the strains IMV B-7241 and IMV Ac-5017 on all studied substrates was accompanied by the increase of conventional con-centration of SAS by 25-140 % as compared with the indices in the medium without copper cations. Maximum synthesis intensification of SAS of A. calcoaceticus IMV B-7241 and R. eiylliropolis IMV Ac-5017 was observed in the case of Cu2+ introduction in the medium with hydrocarbons. The increase of SAS synthesis in the presence of copper cations is determined by their activating effect on activity of alkane hydroxylase of the both strains, as well as 4-nitroso-N,N-dimethyl-aniiine-dependent alcohol dehydrogenase and enzymes of biosynthesis of surface active glyco- (phosphoenolpyruvate-syntlietase) and aininolipids (NADP+-dependent glutamate dehydrogenase) in A. calcoaceticus IMV B-7241.
Keywords: поверхностно-активные вещества; катионы меди; surfactants; copper cations; кафедра біотехнології і мікробіології